Gut microbiota alterations may increase the risk of prescription opioid use, but not vice versa: A two-sample bi-directional Mendelian randomization study - Lin, Liling; Lin, Jianwei; Qiu, Junxiong; Wei, Feng; Bai, Xiaohui; Ma, Weiying; Zeng, Jingxian; Lin, Daowei (Frontiers in Microbiology, 2022)
Gut microbiota alterations are strongly associated with prescription opioid use (POU) and multisite chronic pain (MCP). However, whether these associations are causal remains unknown. Aiming to comprehensively investigate their causal relationships, we conducted a two-sample bi-directional Mendelian randomization to assess the potential associations between gut microbiota and POU/MCP using Genome-wide association studies (GWASs) that were based on predominantly European ancestry. Potential causal effects were identified between seven host genetic-driven traits of gut microbiota on POU, including Adlercreutzia, Allisonella, Dialister, Anaerofilum, Anaerostipes, ChristensenellaceaeR.7group, and LachnospiraceaeNC2004group at the genus level (P < 0.05) by the Inverse-variance weighted method, with significant causal effects of ChristensenellaceaeR.7group and Allisonella on POU (P < 0.025). A total of five genetically greater abundance of gut microbiota traits were identified to be possibly related to the level of MCP (P < 0.05), including genus ErysipelotrichaceaeUCG003, family Clostridiaceae1, order Gastranaerophilales, order Actinomycetales, and family Actinomycetaceae. In the other direction, no clear evidence was found to support a significant causal relationship between POU and gut microbiota, as well as MCP and gut microbiota. In addition, evidence was also provided for the relationship between triacylglycerols and diacylglycerol elevation, and an increased risk of POU and MCP. No evidence was found across various sensitivity analyses, including reverse causality, pleiotropy, and heterogeneity. The findings from this study provide robust evidence to prove that gut microbiota alterations may be a risk of POU/MCP, but not vice versa.